Overcoming the crime of motor vehicle theft in the legal area of minas police Siak district - Rohya Lisma Sihotang (Requisitoire Law Enforcement, 2023)
Countermeasures are efforts made to prevent, dealing with, or overcoming a situation includes preventive activities and at the same time seeks to improve the behavior of someone who has been found guilty (as an inmate) in a correctional institution, in other words efforts to tackle theft can be carried out preventively and regressively. Preventive control has the goal of taking steps to prevent violations of norms, while repressive control has the goal of taking action against violations of norms, so as to create a deterrent effect for the perpetrators. Countermeasures are a prevention that is useful to minimize the events or actions that have occurred so that these events or actions do not occur again. The author chooses this type of observational research by means of direct survey writer to obtain primary data and secondary data. In collecting data, the authors interviewed several respondents, namely: Head of Criminal Investigation Unit, Members of the Police, and Actors. The results of the research that the authors get, there are several factors that cause perpetrators to commit crimes of motor vehicle theft, namely: internal factors (Education, individuals), external factors (economy, environment, global developments). The modus operandi for tackling the crime of motor vehicle theft is: pretending to borrow/rent a motorbike, using the T key, stalking, following and then blocking potential victims, making credit with fake identities, spreading nails on certain roads, looking for a place to live in an area.